(untitled) (Journal of University Teaching and Learning Practice, 2026)
This study investigates the teaching approaches used by faculty members at a Latin American university to identify distinct pedagogical profiles influenced by demographic, disciplinary, and institutional factors. Data were collected from 385 university lecturers using the Approaches to Teaching Inventory (S-ATI-20) within a quantitative, cross-sectional design. The analysis revealed three faculty profiles that differ in how they balance content delivery with student engagement, the extent of their pedagogical preparation, and their use of reflective teaching practices. These results suggest that teaching approaches are shaped not only by academic background and professional experience, but also by the degree of institutional support available to lecturers. While grounded in a Latin American setting, the study offers insights that may guide faculty development and teaching policy in a wide range of higher education institutions facing similar challenges.